Training Needs of Pesticide Retailers in Manipur (Indian Journal of Extension Education, 2013)
Agricultural input dealers as para extension workers play a very useful role. Besides serving the farmers, they can contribute towards strengthening the Agricultural Extension System. However, they need to be equipped with latest know how through refresher training. The present study was conducted during 2013 in Manipur to ascertain training needs of pesticide retailers. Data was collected through personal interview of 109 retailers using structured interview schedule. Respondents were found to be highly educated with as much as 51 per cent having graduate and post-graduate degrees. Around 49 per cent of the respondents mobilized their own resources for the business and only 22 per cent sought bank credit. Risk bearing ability, achievement motivation, knowledge and aspiration level of the pesticide retailers were at medium level. Identification of different pest and pesticides emerged as the most needed training area followed by IPM techniques. Among crop specific training need, vegetable crops ranked first followed by rice. Respondents also reported that training on application of ICTs in business is important. Seasonality in the business of pesticide, lack of need-based training and higher transportation cost were some of the constraints identified by the pesticide retailers in Manipur.